2014
DOI: 10.14233/ajchem.2014.15829
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly Dyeing of UV-Irradiated Cotton Using Extracts of Acacia nilotica Bark (Kikar) as Source of Quercetin

Abstract: Increasing awareness about safe products in textiles has developed the worldwide choice in natural colour based textiles. For the present study, barks of Acacia nilotica (Kikar) has been selected as source of natural flavone dye (querecetin). Both cotton fabrics and dye powder were exposed to UV radiations for 30, 45, 60, 90 and 120 min. Later on the dye was extracted using irradiated (RP) and un-irradiated dye powder (NRP) followed by dyeing of irradiated (RC) and un-irradiated fabric (NRC). Different dyeing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…Many plant which extracted dyes have antioxidant, antimicrobial properties are used in various walks of life, well known for their health curing characterization. Studies on their characterization are also going on the way (Farizadeh et al 2009;Adeel et al 2014;Adeel et al 2013).…”
Section: Eco-friendly Dyeing Of Gamma Raymentioning
confidence: 99%
“…Many plant which extracted dyes have antioxidant, antimicrobial properties are used in various walks of life, well known for their health curing characterization. Studies on their characterization are also going on the way (Farizadeh et al 2009;Adeel et al 2014;Adeel et al 2013).…”
Section: Eco-friendly Dyeing Of Gamma Raymentioning
confidence: 99%
“…Saxena [7] also added that not only natural dyes are biodegradable, the residual vegetal matter after the extraction process could easily be composed or used as fertilizers. Besides the conventional boiling water extraction, natural dyes have been extracted using alternative methods such as using gamma, ultraviolet (UV), microwave and ultrasonic machines that may be able to save energy with low-temperature processing [8,9]. Researchers have also found that certain natural dyes have unique properties such as antimicrobial [10,11,12], insect repellent [13], deodorizing effects [14], and UV-protection [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the conventional extraction methods are eco‐friendly, however, these methods are time consuming labor intensive and not cost effective . The utilization of new techniques such as ultraviolet , microwave , ultrasonic , plasma , and gamma radiations have given a promising effect in natural dyeing process. Of these tools, ultrasonic radiation is taking as a convenient and energy saving method .…”
Section: Introductionmentioning
confidence: 99%